2013
DOI: 10.1007/s10463-013-0416-y
|View full text |Cite
|
Sign up to set email alerts
|

On data depth in infinite dimensional spaces

Abstract: The concept of data depth leads to a center-outward ordering of multivariate data, and it has been effectively used for developing various data analytic tools. While different notions of depth were originally developed for finite dimensional data, there have been some recent attempts to develop depth functions for data in infinite dimensional spaces. In this paper, we consider some notions of depth in infinite dimensional spaces and study their properties under various stochastic models. Our analysis shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…There are a few other notions of depth function for data in infinite dimensional function spaces (see, e.g., [16,25,26] and [32]). However, as shown in [10], some of these depth functions exhibit degeneracy for certain types of functional data, and hence are not very useful.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few other notions of depth function for data in infinite dimensional function spaces (see, e.g., [16,25,26] and [32]). However, as shown in [10], some of these depth functions exhibit degeneracy for certain types of functional data, and hence are not very useful.…”
Section: 2mentioning
confidence: 99%
“…The properties of the spatial depth discussed above imply that it induces a meaningful center-outward ordering of the points in these spaces, and can be used to develop depth-based statistical procedures for data from such distributions. On the other hand, many of the well-known depths for infinite dimensional data like the half-space depth, the band depth and the halfregion depth do not possess such regular behavior and exhibit degeneracy for many Gaussian distributions (see [10]).…”
Section: 2mentioning
confidence: 99%
“…The research has been focused on computational issues, and the only major theoretical results are the consistency theorems: López-Pintado and Romo (2009, Theorem 4) for band depth and López-Pintado and Romo (2011, Theorem 3) for half-region depth. Recently, Chakraborty and Chaudhuri (2014, Section 3) pointed out some degenerate behaviour of the band depth and the half-region depth for certain probability distributions. For Φ-depths of Mosler and Polyakova (2012) there are, as far as we know, no results, yet, on treating its theoretical statistical properties.…”
Section: Introduction: Depth For Functional Datamentioning
confidence: 99%
“…Moreover an interesting question in such a scenario is the identification of an outlier. A study on data depth by Chakraborty & Chaudhuri () showed that for a large class of infinite‐dimensional distributions, the notion of SPD transforms all values to the interval false(0,1false); see their Theorems 6 and 7. SPD is therefore still meaningful for data arising from a quite large class of infinite‐dimensional distributions.…”
Section: Robust Multivariate Regression For Sparse Datamentioning
confidence: 99%